The SARD-SC Project: "Increase yields and alleviate poverty among the African farmers" - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Chrysantus Akem, SARA-SC Project Coordinator, IITA, talks about the SARD-SC project across Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/